PERANCANGAN SISTEM PENJUALAN PADA TOKO ROTI CHIKA BERBASIS WEBSITE - Sihotang, Lady Rachael Yemima; Nainggolan, Rena; Purba, Eviyanti Novita (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The development of computer technology and science has had a positive impact on various areas of human life, including the food industry. One form of this development is the existence of an online bakery that makes it easier for consumers to order bread without having to come to the store. This study aims to design a web-based sales system at Chika Bakery using the PHP programming language and MySQL database. This system will manage data on sales, inventory, purchases, and sales reports. Identification of problems is done to overcome the obstacles that exist in the bakery sales process. The purpose of this research is to design and implement a web-based sales system, analyze the effectiveness and efficiency of the system, provide solutions to the problems encountered, and provide recommendations for improvements. This research uses the method of observation and literature study in data collection. The results of the research will assist shop owners in facilitating the transaction process, increasing market reach, facilitating sales monitoring and reporting, increasing customer trust, and increasing the author's knowledge and skills in designing web-based systems.